Regulation of TSHR Expression in the Thyroid and Thymus May Contribute to TSHR Tolerance Failure in Graves' Disease Patients via Two Distinct Mechanisms - Marín-Sánchez, Ana; Álvarez-Sierra, Daniel; González, Oscar; Lucas-Martin, Ana; Sellés-Sánchez, Alicia; Rudilla, Francesc; Enrich, Emma; Colobran, Roger; Pujol-Borrell, Ricardo (Frontiers in Immunology, 2019)
Graves' disease (GD) involves the presence of agonistic auto-antibodies against the thyrotropin receptor (TSHR), which are responsible for the clinical symptoms. While failure of TSHR tolerance is central to GD pathogenesis, the process leading to this failure remains poorly understood. Two mechanisms intimately linked to tolerance have been proposed to explain the association of SNPs located in TSHR intron 1 to GD: 1) differential alternative splicing in the thyroid; and 2) modulation of expression in the thymus. To elucidate the relative contribution to these two mechanisms to GD pathogenesis, we analyzed the level of full-length and ST4 and ST5 isoform expression in the thyroid (n = 49) and thymus (n = 39) glands, and the influence of intron 1-associated SNPs on such expression. The results show that: 1) the level of flTSHR and ST4 expression in the thymus was unexpectedly high (20% that of the thyroid); 2) while flTSHR is the predominant isoform, the levels are similar to ST4 (ratio flTSHR/ST4 = 1.34 in the thyroid and ratio flTSHR/ST4 in the thymus = 1.93); 3) next-generation sequencing confirmed the effect of the TSHR intron 1 polymorphism on TSHR expression in the thymus with a bias of 1.5 ± 0.2 overexpression of the protective allele in the thymus compared to the thyroid; 4) GD-associated intron 1 SNPs did not influence TSHR alternative splicing, including flTSHR, ST4, and ST5 in the thyroid and thymus; and 5) three-color confocal imaging showed that TSHR is associated with both thymocytes, macrophages, and dendritic cells in the thymus. Our findings confirm the effect of intron 1 polymorphisms on thymic TSHR expression and we present evidence against an effect on the relative expression of isoforms. The high level of ST4 expression in the thymus and its distribution within the tissue suggest that this would most likely be the isoform that induces central tolerance to TSHR thus omitting most of the hinge and transmembrane portion. The lack of central tolerance to a large portion of TSHR may explain the relatively high frequency of autoimmunity related to TSHR and its clinical consequence, GD.